If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -2) = 2(x + -4(x + -2) + x) Reorder the terms: -2(-2 + x) = 2(x + -4(x + -2) + x) (-2 * -2 + x * -2) = 2(x + -4(x + -2) + x) (4 + -2x) = 2(x + -4(x + -2) + x) Reorder the terms: 4 + -2x = 2(x + -4(-2 + x) + x) 4 + -2x = 2(x + (-2 * -4 + x * -4) + x) 4 + -2x = 2(x + (8 + -4x) + x) Reorder the terms: 4 + -2x = 2(8 + x + -4x + x) Combine like terms: x + -4x = -3x 4 + -2x = 2(8 + -3x + x) Combine like terms: -3x + x = -2x 4 + -2x = 2(8 + -2x) 4 + -2x = (8 * 2 + -2x * 2) 4 + -2x = (16 + -4x) Solving 4 + -2x = 16 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4 + -2x + 4x = 16 + -4x + 4x Combine like terms: -2x + 4x = 2x 4 + 2x = 16 + -4x + 4x Combine like terms: -4x + 4x = 0 4 + 2x = 16 + 0 4 + 2x = 16 Add '-4' to each side of the equation. 4 + -4 + 2x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 16 + -4 2x = 16 + -4 Combine like terms: 16 + -4 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 2(4w+1)=-10(x-3)+4 | | 17-5m=5+6m | | 12h^2=2h+4 | | 5x-(-x-3)+2=7(2x+4)-19 | | 6x-1=o | | 3a=5+35-7a | | -18=z-3 | | 28=-(3x+5) | | -7-x=21 | | 2*-4/10= | | (x+2)/14+(x-2)/6=2 | | 38=7g+3.77 | | 7.93-15.20=0.66v | | z^5=iz | | 11.2(3x+3)=3(2x+2) | | (6x+1)+(12x+5)=32 | | -3(r-6)=-47 | | 10.3x+1=3(x-1)+4 | | b-2+2b=30 | | 2x=5y+3 | | 0.5p-1.4=1.5p | | 4.1=8.3-0.6x | | 5x+6x-9=24 | | ln(x+1)=ln(x-3)+1.3 | | 4+2.2h=-3.4 | | 3x+x-12=8 | | 2x+4-x=37 | | 600x+200y=2800 | | x^3-6x^2-9x+154=0 | | 100x+100y=200 | | -8-2+16v=-52 | | x-5-9=20 |